Therapeutic potential of sustainable zinc oxide nanoparticles biosynthesized using Tradescantia spathacea aqueous leaf extract - Sultana Sumreen; Ashwini Bagepalli Shivaram; Hani Umme; Haider Nazima; Alomary Mohammad Nasser; Bhavana Venkateshppa; Daruka Prasad Bangari; Ravikiran Tekupalli; Ansari Mohammad Azam; Lakshmeesha Thimappa Ramachandrappa (Green Processing and Synthesis)
The present study focused on the synthesis of zinc oxide nanoparticles (ZnO NPs) utilizing an aqueous extract (leaves) of Tradescantia spathacea and assessed their antibacterial and anticancer activities. The characterization of NPs was performed using XRD, UV-Vis spectroscopy, Fourier-transform infrared, scanning electron microscopy-energy-dispersive X-ray analysis, and HRTEM with selected area electron diffraction. The antibacterial activity of ZnO NPs was evaluated using the disc diffusion method and the trypan blue dye exclusion method. The anticancer effects in HeLa cells were assessed using the MTT assay, while cellular uptake was assessed through Rhodamine B isothiocyanate-labeled ZnO NPs. The cytotoxic properties of NPs were assessed by estimating the mitochondrial membrane potential (MMP) and apoptosis by Hoechst, propidium iodide, Annexin V-FITC staining, and cell cycle distribution. The synthesized NPs exhibited antibacterial ability with the highest inhibition zone measuring 13.2 mm at a concentration of 1 mg·mL−1. The MTT assay on HeLa cells showed dose-dependent viability ranging from 88% to 24%, with an IC50 value of 84.26 μg·mL−1. JC-1 and Hoechst staining assays confirmed the impairment of MMP and apoptosis, with significant cell cycle arrest observed in the Sub G0/G1, S, and G2/M phases, indicating a disruption in the regular cell cycle. In conclusion, green-synthesized ZnO NPs displayed significant antibacterial and anticancer properties, emphasizing their potential for use in biomedicine and healthcare applications.